2020
DOI: 10.1001/jama.2020.12746
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Incidence of Stillbirth and Preterm Delivery During the COVID-19 Pandemic

Abstract: High rates of preterm birth and cesarean delivery have been reported in women with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. 1 However, studies have inadequate power to assess uncommon outcomes like stillbirth (fetal death ≥24 weeks' gestation). The UK Obstetric Surveillance System reported 3 stillbirths among 247 completed pregnancies in women with confirmed coronavirus disease 2019 (COVID-19) vs the national rate (12.1 per 1000 births vs 4-5 per 1000 births). 2 We assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
461
11
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(532 citation statements)
references
References 5 publications
17
461
11
10
Order By: Relevance
“…3 The absence of an increased prevalence of preterm birth is concordant with results of 2 previous studies using comparators. 4,5 The lack of difference in Apgar scores and birth weight for gestational age between groups is similar to that in a US study. 4 a Direct matching on multiple births and on a propensity score including maternal age, parity, early-pregnancy body mass index, educational level, country of birth, smoking status, living with partner, and prepregnancy comorbidity (yes/no).…”
supporting
confidence: 80%
“…3 The absence of an increased prevalence of preterm birth is concordant with results of 2 previous studies using comparators. 4,5 The lack of difference in Apgar scores and birth weight for gestational age between groups is similar to that in a US study. 4 a Direct matching on multiple births and on a propensity score including maternal age, parity, early-pregnancy body mass index, educational level, country of birth, smoking status, living with partner, and prepregnancy comorbidity (yes/no).…”
supporting
confidence: 80%
“…Regardless, these reports of reductions in emergency antenatal attendances are consistent with other reports of reduced attendances with acute presentations, 28 and are informative particularly in the context of local reports of an increase in stillbirth. 29…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A single-centre study demonstrated a significant increase in the rate of stillbirths, suggesting that this was one adverse outcome. 29 It is unclear whether this was related to the direct effects of COVID-19, or indirectly due to reduced antenatal appointments or attendances for urgent care. The RCOG/RCM guidance advised that the frequency of antenatal appointments should be reduced in a structured fashion, when staffing shortages precluded offer of the standard NICE schedule; 30 31 the risk of perinatal mortality increases if the number of antenatal appointments falls below six.…”
Section: Interpretation (In Light Of Other Evidence)mentioning
confidence: 99%
“…Those experiencing stillbirth and infant mortality did not show symptoms of COVID-19, suggesting these outcomes may instead be due to the reallocation of medical resources towards COVID-19 patients and the subsequent reduction in hospitalization for labor management and perinatal care visits. 73,74 Likewise, another observation is attributed to reduced care: the consistent reductions in preterm birth were seen across various time windows surrounding the implementation of COVID-19 mitigation measures in different countries such as Netherlands, Ireland and Denmark. 104 Some authors discussed reduced air pollution and maternal stress during pregnancy.…”
Section: Prenatal Carementioning
confidence: 96%